SNP2-Lys-C markers inheritance, genes expression, and the resistance of second-generation Catfish Clarias gariepinus against Aeromonas hydrophila infection - Yudha Hanggara; Alimuddin Alimuddin; Dinar Tri Soelistyowati Tri Soelistyowati; Sri Nuryati (Jurnal Akuakultur Indonesia)
High mortality rates in catfish seed caused by motile Aeromonas septicemia disease caused by Aeromonas hydrophila infection. The primary focus is on the genetic selection of the second generation (G2) catfish for resistance to A. hydrophila, utilizing the type-C lysozyme gene at SNP-2 genotype TT. The objective is to assess the inheritance of the SNP2-Lys-C genetic marker from the first generation (G1) Sangkuriang breeders and to evaluate the resistance of the G2 seed to infection. In the experiment, G1 breeders with the TT genotype were spawned, and the resulting G2 seed were challenged with A. hydrophila. The findings indicate that all G2 seed possess the TT genotype and exhibit a higher survival rate compared to the dominant CT genotype seed. The expression of the Lys-C gene in G2 seed is elevated at the onset of infection, decreasing after the seventh day. The expression of the MHC1a and IL-1b genes is also associated with a higher survival rate. The survival of G2 seed correlates with the white blood cell and lysozyme activity, along with an increase in phagocytic activity peaking on the seventh day post-challenge. The conclusion of this study suggests that G2 catfish seed with the TT genotype have stronger resistance to A. hydrophila infection compared to seed with the dominant CT genotype.